Sexual violence in armed conflicts under Criminal Law and International Law - Miró Quesada Gayoso, Josefina (2019)
This article studies sexual violence as a weapon of war perpetrated in contexts of armed conflicts and analyzes, based on the Peruvian case, the applicable legal framework to prosecute and punish such acts during the non international armed conflict between 1980-2000 under the light of national and international criminal law and international human rights law. According to the Final Report of the Truth and Reconciliation Comission, in certain areas, this violence qualified as crimes against humanity and war crimes. Judging these only under the criminal statute applicable at the time of the events is insufficient for the State’s international obligations to prosecute and punish this phenomenon. Thus, it is suggested, the use of international standards that gives content to the national statute, as well as an alternative interpretation of the principle of legality that allows apprehending its real socio-legal devaluation.